A TBR1-K228E Mutation Induces Tbr1 Upregulation, Altered Cortical Distribution of Interneurons, Increased Inhibitory Synaptic Transmission, and Autistic-Like Behavioral Deficits in Mice - Yook, Chaehyun; Kim, Kyungdeok; Kim, Doyoun; Kang, Hyojin; Kim, Sun-Gyun; Kim, Eunjoon; Kim, Soo Young (Frontiers in Molecular Neuroscience, 2019)
Mutations in Tbr1, a high-confidence ASD (autism spectrum disorder)-risk gene encoding the transcriptional regulator TBR1, have been shown to induce diverse ASD-related molecular, synaptic, neuronal, and behavioral dysfunctions in mice. However, whether Tbr1 mutations derived from autistic individuals cause similar dysfunctions in mice remains unclear. Here we generated and characterized mice carrying the TBR1-K228E de novo mutation identified in human ASD and identified various ASD-related phenotypes. In heterozygous mice carrying this mutation (Tbr1+/K228E mice), levels of the TBR1-K228E protein, which is unable to bind target DNA, were strongly increased. RNA-Seq analysis of the Tbr1+/K228E embryonic brain indicated significant changes in the expression of genes associated with neurons, astrocytes, ribosomes, neuronal synapses, and ASD risk. The Tbr1+/K228E neocortex also displayed an abnormal distribution of parvalbumin-positive interneurons, with a lower density in superficial layers but a higher density in deep layers. These changes were associated with an increase in inhibitory synaptic transmission in layer 6 pyramidal neurons that was resistant to compensation by network activity. Behaviorally, Tbr1+/K228E mice showed decreased social interaction, increased self-grooming, and modestly increased anxiety-like behaviors. These results suggest that the human heterozygous TBR1-K228E mutation induces ASD-related transcriptomic, protein, neuronal, synaptic, and behavioral dysfunctions in mice.